2012
DOI: 10.1007/s00018-012-0999-0
|View full text |Cite
|
Sign up to set email alerts
|

Floral meristem initiation and emergence in plants

Abstract: Plant development and architecture is regulated by meristems that initiate lateral organs on their flanks. The gene regulatory networks that govern the transition of a vegetative shoot apical meristem into an inflorescence meristem (IM), together with those necessary to specify floral meristem (FM) identity have been elucidated in Arabidopsis thaliana and are highly complex and redundant. FMs are initiated in the axils of cryptic bracts and evidence suggests that FMs emerge and differentiate along an abaxial/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 125 publications
(135 reference statements)
1
39
0
1
Order By: Relevance
“…1). In A. thaliana, 397 the floral primordium emerges as a cryptic bract, but bracts do not outgrow due to the development 398 of the associated floral meristem (Chandler, 2012). Thus, bracts in A. thaliana only appear in mutants 399 with compromised floral meristem identity (Mandel et al, 1992;Weigel et al, 1992;Chandler, 2012;400 Müller-Xing et al, 2014).…”
Section: Extended Vernalization Ensures Floral Commitment During Coldmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In A. thaliana, 397 the floral primordium emerges as a cryptic bract, but bracts do not outgrow due to the development 398 of the associated floral meristem (Chandler, 2012). Thus, bracts in A. thaliana only appear in mutants 399 with compromised floral meristem identity (Mandel et al, 1992;Weigel et al, 1992;Chandler, 2012;400 Müller-Xing et al, 2014).…”
Section: Extended Vernalization Ensures Floral Commitment During Coldmentioning
confidence: 99%
“…In A. thaliana, 397 the floral primordium emerges as a cryptic bract, but bracts do not outgrow due to the development 398 of the associated floral meristem (Chandler, 2012). Thus, bracts in A. thaliana only appear in mutants 399 with compromised floral meristem identity (Mandel et al, 1992;Weigel et al, 1992;Chandler, 2012;400 Müller-Xing et al, 2014). In A. alpina, the number of bracts in the I2 zone was reduced after longer 401 vernalization periods, following an opposite pattern to the expression of floral identity genes in the 402 www.plantphysiol.org on May 12, 2018 -Published by Downloaded from Copyright © 2018 American Society of Plant Biologists.…”
Section: Extended Vernalization Ensures Floral Commitment During Coldmentioning
confidence: 99%
“…Throughout their development, leaves undergo different growth stages to mature into planar, photosynthetic organs organized in a flat rosette with little overlap (Figure 1) . When transitioning to the reproductive, flowering stage, the vegetative SAM transforms into an inflorescence meristem that gives rise to cauline leaves and flowers (Alvarez-Buylla et al, 2010;Chandler, 2012). The small size of Arabidopsis and its short life span facilitate numerous quantitative phenotyping methods.…”
Section: The Arabidopsis Rosettementioning
confidence: 99%
“…Arabidopsis is unusual in that its flowers are not subtended by a leaf-like organ termed a bract. However, detailed analysis has suggested that after the floral transition, the youngest primordia to arise on the flanks of the inflorescence meristem are leaf-like organs, which usually do not grow out during later flower stages and hence are termed cryptic bracts (Figure 1) (Long and Barton, 2000;Kwiatkowska, 2006;Chandler, 2012). The different types of reversion nodes observed in the Pc-G mutants likely reflect the time at which floral primordium identity is compromised and reversion occurs.…”
Section: Differing Roles Of Flc and Svp In Reversionmentioning
confidence: 99%
“…After floral induction, flower production is stable even if plants are shifted from LD to SD. (B) to (E) Development of the flower metamers (according to Smyth et al [1990], Chandler [2012], and Long and Barton [2000]): In stage 1 (B), the floral primordium emerges as cryptic bract (CB) and thus has leaf-like identity. In early stage 2 (C), the FM develops between the IM and the cryptic bract.…”
Section: Introductionmentioning
confidence: 99%